32-38 Faneuil Hall Square, 1857 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking northeast toward several shops in Faneuil Hall Square. The building on the left edge of the photograph is the Old Feather Store. Several people are standing on the sidewalks in front of the shops. Horse-drawn vehicles are seen on the cobblestoned streets in the area. Image is part of the Henry P. Curtis Collection. 10 1/8 x 14 Photographs